Pelatihan Pengisian KSPR Kader Berpengaruh terhadap Keterampilan Deteksi Dini Kehamilan Resiko Tinggi - Kusmiwiyati, Ari; Jupriyono, Jupriyono (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2020)
The presence of health cadres in early detection of high risk pregnancies is important to identify possible complications of pregnant women. Not all cadres have the skills in early detection of high-risk pregnancies. In this case, it is necessary to make efforts to increase knowledge and skills through training in filling out the Poedji Rochjati Score Card. The aim of the study was to determine the effect of training in filling out pregnancy risk assessments on the skills of posyandu cadres in early detection of high-risk pregnancies. The pre-experimental research design used the one group pretest-posttest design approach, with a population of all Posyandu cadres in Ampeldento. The sampling used a total sampling technique with a sample size of 30 respondents. The research instrument used the Poedji Rochjati Scorecard and checklist. Data analysis used the Wilcoxon Signed Rank Test. The results showed that there was an effect of training in filling out pregnancy risk assessments on the skills of Posyandu cadres in early detection of high-risk pregnancies (p value <0.001 with Z score -4.630). Cross-program and sectoral coordination is needed in implementing cadre skills in early detection of risky pregnancies. Keywords: Pregnancy Risk Assessment Training, Early Detection of Risk Pregnancy